Propuesta de un plan estratégico para los servicios de capacitación continua en la empresa pública La Nacional de Loja-EP, para el periodo 2024-2028. - Ortega Gaona, Fabián de Jesús (2024)
The general objective of the research work carried out at La Nacional de Loja-EP, the first public company of the National University of Loja, was to formulate a strategic plan for the continuous training services of the public company “La Nacional-EP” of the Loja canton, for the period 2024- 2028. Two specific objectives were defined for its fulfillment: the first, to determine the current situation of the continuous education services of the public company La Nacional-EP and the second: to elaborate the strategic plan for the continuous education services of the public company La Nacional-EP, based on the results of the diagnosis carried out. The methodology used was based on the mixed approach of non-experimental design with an exploratory-descriptive and cross- sectional scope; using data collection techniques and tools such as interviews, focus group, document review, stakeholder map, Porter's 5 forces matrix, PESTEL analysis, Opportunities and Threats of the Environment Profile matrix (POAM), Internal Capacity Profile matrix (PCI) and the prioritization of internal and external factors with the Pareto 80/20 principle for the construction of the SWOT matrix in which 10 strengths, 17 opportunities, 6 weaknesses and 8 threats were diagnosed; the strategic direction of the public company was then formulated, including the guiding elements (mission, vision and values), the 4 strategic objectives with their respective policies, strategies and operational objectives. Giving life to the strategic plan segmented in two phases, the situational diagnosis and the strategic direction with the elements previously described and adding the action plan that contains the breakdown of the objectives with their respective indicators, formulas, goals, actions and responsible departments, as well as the strategic projects that will help the fulfillment of the strategic objectives.